Tin-lead perovskite photoelectric detector based on introduction of guanidine ions and strontium ions and preparation method thereof
By introducing guanidine ions and strontium ions into the perovskite photodetector, the problem that the perovskite photodetector cannot effectively detect infrared light is solved, and the photoelectric conversion efficiency is improved and the device stability is optimized.
Patent Information
- Application Number
- CN202510060330.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-15
AI Technical Summary
Due to the limitation of band gap, existing perovskite photodetectors cannot effectively detect infrared light, which limits their application potential in medical imaging and communication technology.
By introducing guanidine ions (GA+) and strontium ions (Sr2+) into the tin-lead perovskite film, doped ions can fill the interface and surface of the perovskite layer, improve carrier life, increase carrier diffusion length, reduce defects, and optimize electrode performance.
The photoelectric conversion efficiency of perovskite photodetectors has been improved, especially in the range of 400 to 1000 nm, the external quantum efficiency has been significantly improved, and the stability and performance of the device have also been optimized.
Smart Images

Figure CN119855458A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite photoelectric devices, and particularly relates to a tin-lead perovskite photoelectric detector based on the introduction of guanidine ions and strontium ions and a preparation method thereof. Background Art
[0002] Photodetectors are devices that use the photoelectric effect to directly convert optical signals into electrical signals. They are widely used in various fields such as military defense, environmental monitoring, and medical communications. For example, in the ultraviolet band, they are mainly used for national defense, forest fire warning, etc.; in the visible or near-infrared band, they are mainly used for imaging, photometry, and automatic control; in the infrared band, they are mainly used for missile guidance, infrared imaging, and remote sensing. With the continuous advancement of science and technology, new requirements have been put forward for the spectrum, flexibility, and performance of photodetectors. The diversified requirements make it difficult for traditional photodetectors represented by silicon to meet them. Therefore, it is necessary to develop new photodetectors to make up for the shortcomings of traditional photodetectors.
[0003] Perovskite materials have photoelectric properties such as high absorption coefficient, high mobility, adjustable band gap, long carrier diffusion length, and the advantages of low cost, light weight, easy processing and bendability of the prepared photodetectors, so they have attracted widespread attention. However, due to the limitation of the band gap, perovskite materials cannot detect infrared light, and infrared light detection has a wide range of applications in fields such as medical imaging and communication technology, which seriously restricts the application potential of perovskite photodetectors. One way to broaden the absorption spectrum of perovskite photodetectors is to dope some divalent tin elements, which can broaden the absorption edge of perovskite to the near-infrared region. Summary of the invention
[0004] The purpose of the present invention is to provide a tin-lead perovskite photodetector based on the introduction of guanidine ions and strontium ions and a preparation method thereof.
[0005] The photodetector designed by the present invention is composed of an ITO conductive glass anode, a PTAA (poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine)) anode buffer layer, a tin-lead perovskite film introduced with guanidine ions and strontium ions, a C 60 / BCP cathode buffer layer and Cu cathode.
[0006] Tin-containing perovskites are characterized by the presence of p-doping from intrinsic and extrinsic sources, which greatly affects many key optoelectronic properties of perovskite devices, such as light-dark current and external quantum efficiency. In addition, due to the characteristics of tin ions, the ubiquitous presence of various defects in its absorption layer may lead to non-radiative trap recombination of charge carriers, thereby reducing the performance of tin-based perovskite devices. Therefore, any attempt to improve the optoelectronic performance of tin-based perovskite devices is mainly aimed at controlling doping and defect passivation. The present invention proposes the introduction of guanidine ions (GA + ) and strontium ions (Sr 2+ ) strategy, doping ions can effectively fill the interface and surface of the perovskite layer, GA + When Sr ions are doped into the A-site cations in perovskite, the carrier lifetime of the perovskite material can be increased, the open circuit voltage of the device can be increased, the carrier diffusion length can be increased, defects can be reduced, and the stability of the device can be improved. 2+ Ion doping in the B site of perovskite can increase conductivity, improve stability, and optimize electrode performance, ultimately achieving the effect of passivating defects, reducing the capture of electrons by traps, and improving photoelectric conversion efficiency. The optimization effect is mainly reflected in the light and dark currents and external quantum efficiency.
[0007] The method for preparing a tin-lead perovskite photodetector based on the introduction of guanidine ions and strontium ions described in the present invention comprises the following steps:
[0008] (1) Place ITO conductive glass (250-350mm 2 ) respectively using acetone, anhydrous ethanol, and deionized water for ultrasonic cleaning for 10 to 40 minutes, then drying with nitrogen to obtain a clean ITO conductive glass, and then treating with ozone ultraviolet for 30 to 40 minutes to obtain an ITO conductive glass anode;
[0009] (2) dissolving 4 to 8 mg of PTAA in 2 to 4 mL of toluene, stirring for 20 to 24 h under the condition of full nitrogen and water oxygen content less than 0.01 ppm, to obtain a toluene solution of PTAA; then, in a nitrogen glove box or in an air environment, using a coating machine to evenly spin-coat the toluene solution of PTAA on an ITO conductive glass anode at a spin-coating speed of 3500 to 4500 rpm for 35 to 45 s, and then annealing on a hot stage at 90 to 110° C. for 10 to 15 min, thereby obtaining a 20 to 40 nm thick PTAA anode buffer layer on the ITO conductive glass anode;
[0010] (3) DMF and DMSO were mixed in a volume ratio of 4:1 to obtain a mixed solvent; the raw materials FAI, PbI2, SnI2, GAI, SrI2 and CsI ... 0.1 FA 0.85 GA0.05 Sr 0.002 Pb 0.499 Sn 0.499 I3 was added to the mixed solvent in a stoichiometric ratio, and then stirred for 20 to 24 hours in a glove box filled with nitrogen and with a water oxygen content of less than 0.01 ppm to obtain a perovskite precursor solution with a concentration of 1 to 1.5 mol / L; then 90 to 120 μL was dripped onto the PTAA anode buffer layer on a sizing machine at 800 to 1200 rpm in a glove box filled with nitrogen. DMF is used for spin coating. After 10 to 15 seconds of spin coating, 60 to 90 μL of the perovskite precursor solution is spin coated on the PTAA anode buffer layer. The spin coating speed of the coating machine is set to 3500 to 4500 rpm, and the spin coating time is 25 to 40 seconds. When the spin coating time is 10 to 15 seconds, 250 to 350 μL of the anti-solvent chlorobenzene is added dropwise. After the spin coating is completed, the device is transferred to a hot stage and annealed at 80 to 120° C. for 10 to 15 minutes, thereby obtaining a high-quality, well-filmed CsO2 with a thickness of 400 to 450 nm on the PTAA anode buffer layer. 0.1 FA 0.85 GA 0.05 Sr 0.002 Pb 0.499 Sn 0.499 I3 tin-lead perovskite film;
[0011] (4) Using a multi-source organic vapor phase molecular deposition system, at a pressure not higher than 7×10 -4 Pa vacuum, a C layer with a thickness of 20 to 40 nm was deposited on the Sn-Pb perovskite film. 60 layer, then in C 60 A BCP layer with a thickness of 5 to 10 nm is then evaporated on the layer to obtain C 60 / BCP cathode buffer layer;
[0012] (5) Using a multi-source organic vapor phase molecular deposition system, at a pressure not higher than 7×10 -4 Pa, at C 60 A Cu cathode with a thickness of 80 to 90 nm is evaporated on the BCP cathode buffer layer, thereby preparing the tin-lead perovskite photodetector based on the introduction of guanidine ions and strontium ions described in the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 : Schematic diagram of the structure of the tin-lead perovskite photodetector based on the introduction of guanidine ions and strontium ions according to the present invention; from bottom to top, it is an ITO conductive glass anode, a PTAA anode buffer layer, a tin-lead perovskite film introduced with guanidine ions and strontium ions, a C 60 / BCP cathode buffer layer and Cu cathode;
[0014] Figure 2: Light absorption characteristic curves of the tin-lead perovskite films prepared in Comparative Example 2 and Example 1; The response spectra of the two tin-lead perovskite films of Comparative Example 2 (curve ①) and Example 1 (curve ②) both cover the range of 300 to 1100 nm and extend to the near-infrared region, providing a practical basis for realizing a wide-spectrum photodetector of visible light-near-infrared light;
[0015] Figure 3 : Cs prepared in Comparative Example 1, Comparative Example 2 and Experimental Example 1 0.15 FA 0.85 Pb 0.5 Sn 0.5 I3、Cs 0.1 FA 0.85 GA 0.05 Pb 0.5 Sn 0.5 I3 and Cs 0.1 FA 0.85 GA 0.05 Sr 0.002 Pb 0.499 Sn 0.499 The external quantum efficiency (EQE) curve of the photodetector of I3 tin-lead perovskite film; it can be seen that the comparative example 2 ( Figure 3 (a) curve ②), Example 1 with the addition of guanidine ions and strontium ions ( Figure 3 (b) curve ②) is better than that of comparative example 1 ( Figure 3 Curve ① of (a) shows a higher external quantum efficiency, while that of comparative example 2 ( Figure 3 Curve ② of (a) is mainly improved in the range of 400 to 1000 nm, with the conversion efficiency exceeding 75% at around 550 nm and exceeding 55% at around 900 nm. Figure 3 (b) Curve ②) is compared with Comparative Example 2 ( Figure 3 Curve ① of (b) is mainly improved at 400-750nm, the EQE at around 580nm is close to 80%, and the conversion efficiency at around 900nm exceeds 60%. It can be seen that the tin-lead perovskite photodetector based on the introduction of guanidine ions and strontium ions prepared by the method of the present invention has good photoelectric conversion ability.
[0016] Figure 4 : JV characteristic curves of the tin-lead perovskite photodetectors prepared in Comparative Example 1, Comparative Example 2 and Experimental Example 1 under light and dark conditions, the voltage scanning range is -400 to 1200 mV, and the horizontal and vertical coordinates of the data image are processed logarithmically; it can be seen that Comparative Example 2 ( Figure 4 The dark current of curve ② of (a) is compared with that of comparative example 1 ( Figure 4 The curve ① of (a) is obviously reduced by one order of magnitude, while the curve ① of Comparative Example 2 ( Figure 4The photocurrent of curve ③ of (a) is compared with that of comparative example 1 ( Figure 4 Curve ④ of (a) reflects the stronger light response characteristic of the device. Figure 4 The dark current of curve ② of (b) is higher than that of comparative example 2 ( Figure 4 The curve ① of (b) continues to decrease by an order of magnitude, reaching 10 -5 ; Comparative Example 2( Figure 4 The photocurrent of curve ③ in (b) is higher than that of comparative example 1 ( Figure 4 Curve ④) of (b) also reflects the characteristics of stronger light response, indicating that the device doped with guanidine ions and strontium ions significantly reduced the voltage loss and increased the open-circuit voltage, resulting in a photodetector with better performance.
[0017] Figure 5 : Noise current test curves of the tin-lead perovskite materials prepared in Comparative Example 1, Comparative Example 2 and Example 1; As can be seen from the figure, Comparative Example 2 ( Figure 5 The curve ② of (a) is better than that of comparative example 1 ( Figure 5 The noise current of curve ① of (a) is reduced by two orders of magnitude. Figure 5 (b) curve ②) is better than that of comparative example 2 ( Figure 5 The noise current of curve ① in (b) is as low as 10 -13 , further proving that the presence of guanidine ions and strontium ions reduces the defects of the perovskite layer and obtains excellent perovskite photodetectors.
[0018] Figure 6 : EQE response curves of the tin-lead perovskite materials prepared in Comparative Example 2 and Example 1 at different times; wherein the EQE selection time of Comparative Example 2 is 1 day ( Figure 6 (a) curve ①), 3 days ( Figure 6 (a) curve ②) and 7 days ( Figure 6 (a) curve ③), the EQE selection time of Example 1 is 1 day ( Figure 6 (b) curve ①), 3 days ( Figure 6 (b) curve ②) and 7 days ( Figure 6 (b) curve ③). As can be seen from the figure, the EQE response decreases with the passage of time. Figure 6 The EQE curve of (a)) decreased by about 10% after 7 days, but still maintained a relatively high device performance; Example 1 ( Figure 6 The peak value of EQE of (b)) remains at 70% after 7 days, while the peak value of EQE of Comparative Example 2 is lower than 70%, which further proves that the presence of guanidine ions and strontium ions improves the stability of the device.
[0019] Figure 7: Atomic force microscope images of the photodetectors of the tin-lead perovskite films prepared in Comparative Example 1, Comparative Example 2 and Example 1; it can be seen that Comparative Example 1 ( Figure 7 (a) The surface of the undoped original control group tin-lead perovskite film is relatively rough, with an average surface roughness (RMS) of about 18.8nm. Figure 7 (b) The average surface roughness of 2 after adding guanidine ion doping is 15.8nm, and that of Example 1 ( Figure 7 (c) The average surface roughness of the film with the addition of guanidine ions and strontium ions is 13.2nm. Such a significant reduction in surface roughness effectively proves the improvement in film forming ability brought about by guanidine ion and strontium ion doping, further enhancing electron extraction and reducing carrier recombination caused by interface defects. DETAILED DESCRIPTION
[0020] Comparative Example 1:
[0021] (1) Place ITO conductive glass (20*15mm, area 300mm 2 ) ultrasonically cleaning with acetone for 30 min, ultrasonically cleaning with anhydrous ethanol for 20 min, and ultrasonically cleaning with deionized water for 10 min, drying with nitrogen to obtain a clean ITO conductive glass, and performing ultraviolet ozone treatment for 30 min to obtain an ITO conductive glass anode;
[0022] (2) 4 mg of PTAA was dissolved in 2 mL of toluene, and the mixture was stirred for 24 h at room temperature in a nitrogen atmosphere with a water oxygen content of less than 0.01 ppm to obtain a toluene solution of PTAA; the toluene solution of PTAA was then evenly spin-coated on the ITO conductive glass anode in a nitrogen glove box, and the parameters of the coating machine were a spin coating speed of 4000 rpm, a spin coating acceleration of 2000 rpm, and a spin coating time of 40 s. After the spin coating was completed, the anode was placed on a preheated hot stage and annealed at 100° C. for 10 min, thereby obtaining a 30 nm PTAA anode buffer layer on the ITO conductive glass anode;
[0023] (3) First, prepare a tin-lead perovskite precursor solution by mixing DMF and DMSO at a volume ratio of 4:1 to obtain a mixed solvent. 0.15 FA 0.85 Pb 0.5 Sn 0.5I3 was added into the mixed solvent in a stoichiometric ratio, and stirred for 24 h in a glove box filled with nitrogen and with a water oxygen content of less than 0.01 PPm to obtain a perovskite precursor solution with a concentration of 1.5 mol / L. Then, in a glove box filled with nitrogen and with a water and oxygen content of less than 0.01 PPm, the parameters of the glue spreader were set to a spin coating speed of 1000 rpm, a spin coating acceleration of 500 rpm, and a spin coating time of 10 s. 100 μL of DMF was added to the PTAA anode buffer layer for spin coating. After 10 s of spin coating, 70 μL of the perovskite precursor solution was spin coated on the PTAA anode buffer layer. The parameters of the glue spreader were set to a spin coating time of 30 s, a spin coating speed of 4000 rpm, and a spin coating acceleration of 2000 rpm. When the spin coating time was 15 s, 300 μL of the anti-solvent chlorobenzene was added. After the spin coating was completed, the device was transferred to a preheated hot stage and annealed at 100 ° C for 10 min to obtain a Cs with a thickness of 410 nm. 0.15 FA 0.85 Pb 0.5 Sn 0.5 I3 tin-lead perovskite film;
[0024] (4) Using a multi-source organic vapor phase molecular deposition system at a pressure not higher than 7×10 -4 Pa, a 20 nm thick C was deposited on the SnPb perovskite film. 60 layer, then in C 60 A BCP layer with a thickness of 7 nm was then evaporated on the layer to obtain C 60 / BCP cathode buffer layer;
[0025] (5) Using a multi-source organic vapor phase molecular deposition system at a pressure not higher than 7×10 -4 Pa, at C 60 Cu with a thickness of 80 nm was evaporated on the / BCP cathode buffer layer as a cathode, thereby preparing a tin-lead perovskite photodetector.
[0026] Comparative Example 2:
[0027] (1) Place ITO conductive glass (20*15mm, area 300mm 2 ) ultrasonically clean the glass with acetone for 30 min, ethanol for 20 min, and deionized water for 10 min, blow dry with nitrogen to obtain a dry and clean ITO conductive glass, and then treat it with ultraviolet ozone for 30 min to obtain an ITO conductive glass anode;
[0028] (2) 4 mg of PTAA was dissolved in 2 mL of toluene, and stirred for 24 h under the condition of full nitrogen and water oxygen content less than 0.01 ppm to obtain a toluene solution of PTAA; then, the toluene solution of PTAA was evenly spin-coated on the ITO conductive glass anode in a nitrogen glove box, and the parameters of the coating machine were a spin coating speed of 4000 rpm, a spin coating acceleration of 2000 rpm, and a spin coating time of 40 s. After the spin coating was completed, it was placed on a preheated hot stage and annealed at 100° C. for 10 min, thereby obtaining a 30 nm PTAA anode buffer layer on the ITO conductive glass anode;
[0029] (3) First, prepare a tin-lead perovskite precursor solution by mixing DMF and DMSO in a volume ratio of 4:1 to obtain a mixed solvent; mix the raw materials FAI, PbI2, SnI2, CsI and GAI in a Cs 0.1 FA 0.85 GA 0.05 Pb 0.5 Sn 0.5 I3 was added to the mixed solvent in a stoichiometric ratio, and stirred for 24 hours in a glove box filled with nitrogen and with a water oxygen content of less than 0.01 PPm to obtain a perovskite precursor solution with a concentration of 1.5 mol / L. Then, in a glove box filled with nitrogen and with a water oxygen content of less than 0.01 PPm, the parameters of the glue machine were set to a spin coating speed of 1000 rpm, a spin coating acceleration of 500 rpm, and a spin coating time of 10 s. 100 μL of DMF was added to the PTAA anode buffer layer for spin coating. After the spin coating was completed for 10 s, 70 μL of the perovskite precursor solution was spin coated on the PTAA anode buffer layer. The parameters of the glue machine were set to a spin coating time of 30 s, a spin coating speed of 4000 rpm, and a spin coating acceleration of 2000 rpm. When the spin coating time was 15 s, 300 μL of the anti-solvent chlorobenzene was added; after the spin coating was completed, the device was transferred to a preheated hot stage and annealed at 100 ° C for 10 min to obtain a Cs with a thickness of 430 nm. 0.1 FA 0.85 GA 0.05 Pb 0.5 Sn 0.5 I3 tin-lead perovskite film;
[0030] (4) Using a multi-source organic vapor phase molecular deposition system at a pressure not higher than 7×10 -4 Pa, a 20 nm thick C was deposited on the SnPb perovskite film. 60 layer, then in C 60 A BCP layer with a thickness of 7 nm was then evaporated on the layer to obtain C 60 / BCP cathode buffer layer;
[0031] (5) Using a multi-source organic vapor phase molecular deposition system at a pressure not higher than 7×10-4 Pa, at C 60 Cu with a thickness of 80 nm was evaporated on the / BCP cathode buffer layer as a cathode, thereby preparing a tin-lead perovskite photodetector.
[0032] Embodiment 1:
[0033] (1) Place ITO conductive glass (20*15mm, area 300mm 2 ) ultrasonically clean the glass with acetone for 30 min, ethanol for 20 min, and deionized water for 10 min, blow dry with nitrogen to obtain a dry and clean ITO conductive glass, and then treat it with ultraviolet ozone for 30 min to obtain an ITO conductive glass anode;
[0034] (2) 4 mg of PTAA was dissolved in 2 mL of toluene, and stirred for 24 h under the condition of full nitrogen and water oxygen content less than 0.01 ppm to obtain a toluene solution of PTAA; then, the toluene solution of PTAA was evenly spin-coated on the ITO conductive glass anode in a nitrogen glove box, and the parameters of the coating machine were a spin coating speed of 4000 rpm, a spin coating acceleration of 2000 rpm, and a spin coating time of 40 s. After the spin coating was completed, it was placed on a preheated hot stage and annealed at 100° C. for 10 min, thereby obtaining a 30 nm PTAA anode buffer layer on the ITO conductive glass anode;
[0035] (3) First, prepare a tin-lead perovskite precursor solution by mixing DMF and DMSO at a volume ratio of 4:1 to obtain a mixed solvent. 0.1 FA 0.85 GA 0.05 Sr 0.002 Pb 0.499 Sn 0.499I3 was added into the mixed solvent in a stoichiometric ratio, and stirred for 24 h in a glove box filled with nitrogen and with a water oxygen content of less than 0.01 PPm to obtain a perovskite precursor solution with a concentration of 1.5 mol / L. Then, in a glove box filled with nitrogen and with a water and oxygen content of less than 0.01 PPm, the parameters of the glue spreader were set to a spin coating speed of 1000 rpm, a spin coating acceleration of 500 rpm, and a spin coating time of 10 s. 100 μL of DMF was added to the PTAA anode buffer layer for spin coating. After 10 s of spin coating, 70 μL of the perovskite precursor solution was spin coated on the PTAA anode buffer layer. The parameters of the glue spreader were set to a spin coating time of 25 s, a spin coating speed of 4000 rpm, and a spin coating acceleration of 2000 rpm. When the spin coating time was 15 s, 250 μL of anti-solvent chlorobenzene was added. After the spin coating was completed, the device was transferred to a preheated hot stage and annealed at 100 ° C for 10 min to obtain a high-quality, well-formed 430 nm thick Cs 0.1 FA 0.85 GA 0.05 Sr 0.002 Pb 0.499 Sn 0.49 9I3 tin-lead perovskite thin film;
[0036] (4) Using a multi-source organic vapor phase molecular deposition system at a pressure not higher than 7×10 -4 Pa, a 20 nm thick C was deposited on the SnPb perovskite film. 60 layer, then in C 60 A BCP layer with a thickness of 7 nm was then evaporated on the layer to obtain C 60 / BCP cathode buffer layer;
[0037] (5) Using a multi-source organic vapor phase molecular deposition system at a pressure not higher than 7×10 -4 Pa, at C 60 Cu with a thickness of 80 nm was evaporated on the / BCP cathode buffer layer as a cathode, thereby preparing a tin-lead perovskite photodetector.
Claims
1. A method for preparing a tin-lead perovskite photodetector based on the introduction of guanidine ions and strontium ions, the steps of which are as follows: (1) The ITO conductive glass is ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water for 10 to 40 minutes, and then dried with nitrogen to obtain a clean ITO conductive glass, and then treated with ozone ultraviolet for 30 to 40 minutes to obtain an ITO conductive glass anode; (2) in a nitrogen glove box or in an air environment, uniformly spin-coating a toluene solution of PTAA on an ITO conductive glass anode, and obtaining a 20-40 nm thick PTAA anode buffer layer on the ITO conductive glass anode after annealing; (3) The raw materials FAI, PbI2, SnI2, GAI, SrI2 and CsI are prepared according to the tin-lead perovskite Cs 0.1 FA 0.85 GA 0.05 Sr 0.002 Pb 0.499 Sn 0.499 I3 is added to the mixed solvent in a stoichiometric ratio, and stirred for 20 to 24 hours in a glove box filled with nitrogen and with a water oxygen content of less than 0.01 PPm to obtain a perovskite precursor solution with a concentration of 1 to 1.5 mol / L; then, 90 to 120 μL of DMF is dripped on the PTAA anode buffer layer at 800 to 1200 rpm in a glove box filled with nitrogen for spin coating, and after 10 to 15 seconds of spin coating, 60 to 90 μL of the perovskite precursor solution is spin coated on the PTAA anode buffer layer, and the spin coating speed is set to 3500 to 4500 rpm, and the spin coating time is 25 to 40 seconds. When the spin coating time is left for 10 to 15 seconds, 250 to 350 μL of anti-solvent chlorobenzene is dripped; after the spin coating is completed, the device is transferred to a hot stage and annealed at 80 to 120° C. for 10 to 15 minutes, thereby obtaining a 400 to 450 nm thick Cs on the PTAA anode buffer layer. 0.1 FA 0.85 GA 0.05 Sr 0.002 Pb 0.499 Sn 0.499 I3 tin-lead perovskite film; (4) At a pressure not higher than 7×10 -4 Pa vacuum, a 20-40 nm thick C layer was deposited on the Sn-Pb perovskite film. 60 layer, then in C 60 A BCP layer with a thickness of 5 to 10 nm is then evaporated on the layer to obtain C 60 / BCP cathode buffer layer; (5) At a pressure not higher than 7×10 -4 Pa, under C 60 A Cu cathode with a thickness of 80 to 90 nm is evaporated on the BCP cathode buffer layer, thereby preparing the tin-lead perovskite photodetector based on the introduction of guanidine ions and strontium ions described in the present invention.
2. The method for preparing a tin-lead perovskite photodetector based on the introduction of guanidine ions and strontium ions as claimed in claim 1, characterized in that: In step (2), 4 to 8 mg of PTAA is dissolved in 2 to 4 mL of toluene, and stirred for 20 to 24 hours under the condition of nitrogen filling and water oxygen content less than 0.01 ppm to obtain a toluene solution of PTAA.
3. The method for preparing a tin-lead perovskite photodetector based on the introduction of guanidine ions and strontium ions as claimed in claim 1, characterized in that: The spin coating speed in step (2) is 3500-4500 rpm, the spin coating time is 35-45 s, and then annealing is performed on a hot stage at 90-110° C. for 10-15 min.
4. The method for preparing a tin-lead perovskite photodetector based on the introduction of guanidine ions and strontium ions as claimed in claim 1, characterized in that: In step (4), DMF and DMSO are mixed in a volume ratio of 4:1 to obtain a mixed solvent.
5. A tin-lead perovskite photodetector based on the introduction of guanidine ions and strontium ions, characterized in that: The method is prepared by any one of claims 1 to 4.
Citation Information
Patent Citations
Perovskite photovoltaic cell, preparation method thereof and preparation method of photoelectric assembly
CN111668375A
Enhanced perovskite materials for photovoltaic devices
CN113272312A
Methylamine lead bromide perovskite single-crystal photoelectric detector based on guanidine iodide doping and preparation method of methylamine lead bromide perovskite single-crystal photoelectric detector
CN117500341A
Flange clamp for semiconductor equipment with constant temperature heating function
KR102334333B1
Enhanced Perovskite Materials for Photovoltaic Devices
US20200161127A1